KARAKTERISTIK GEL-NANOLIPOSOM MINYAK ROSEMARI (Rosmarinus officinalis) UNTUK FORMULASI SEDIAAN PENINGKATAN PERTUMBUHAN RAMBUT - Baruna, Renno Ramadhani Ika; Ramadani, Arba Pramundita; Chabib, Lutfi (MEDFARM: Jurnal Farmasi dan Kesehatan, 2024)
Hair loss occurs in many people, both men and women. Rosemari (Rosemarinus officinalis) is one of the plants shown to significantly improve hair growth in alopecia patients. Nanoliposome gel can enhance the activity of bioactive agents by increasing solubility, bioavailability, stability and preventing unnecessary interactions with other molecules in cosmetic preparations. The purpose of this study was to determine the physical characteristics and stability of nanoliposome gel as a carrier of rosemary oil produced. The nanoliposome formulations were evaluated: organoleptical, particle size and zeta potential, and morphological tests. The results of the physical characteristics of nanoliposomes in the form of a slightly cloudy clear gel, semi-liquid texture and typical aromatic odor of rosemary, particle size of 210.5 nm, zeta potential of -23.2 nV, and spherical morphology. Rosemary oil nanoliposome gel preparation has good physical characteristics and stability, so it can be used as a preparation formulation for hair growth.